LEVEL OF COMPETENCY IN TOUR GUIDING AMONG FOURTH YEAR STUDENTS IN BESTLINK COLLEGE OF THE PHILIPPINES - BULACAN CAMPUS. (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study aims to assess the level of competency in tour guiding among fourth-year students at Bestlink College of the Philippines - Bulacan Campus. Tour guiding requires practical and hands-on skills, making it essential for students to develop their competencies through actual experiences. This research examines the competencies needed for students to effectively guide tours and enhance their skills in the tourism industry. The researchers employed a quantitative research method with a descriptive research design. Purposive sampling was used to select respondents, which included tourists, community members, and head teachers. A survey questionnaire was distributed to 25 respondents, with females comprising 92% of the sample and males only 8%. This gender disparity suggests that the findings may be influenced by the predominance of female perspectives, potentially affecting experiences, opinions, and behaviors related to tour guiding. Enhancing competency in tour guiding requires developing approaches that engage students, foster learning, and create memorable experiences. Knowledgeable tour guides help deepen understanding and appreciation of subjects such as history, art, science, and culture, making educational tours more enriching. Graduating students must develop both theoretical knowledge and practical skills to succeed in the tourism industry. A strong academic background in geography, history, and culture is crucial for designing educational and engaging tours. However, the transition from theoretical learning to real-world application remains a challenge. To address this, educational institutions should incorporate more experiential learning opportunities, such as simulations, internships, and direct interaction with tourists, to better prepare students for the demands of the tourism sector.
Keywords: competency; tour guiding; experience; knowledge